The Effect of Culture Orientation and Social Support on Work Behavior, Work Value and Performance of Family Waste Management In Tegal Regency - Jalil, Mahben; Ujianto,; Nugroho, Riyadi (Archives of Business Research, 2019)
The problem of family waste is a fairly complicated problem for most cities in Indonesia. Waste is a problem that needs special attention. Because if family waste is not managed properly it will have a large negative effect on health. The Tegal Regency Government has a special agency that is responsible for family waste management in Tegal Regency, namely the Department of Environment for Spatial Planning, Landscaping and Hygiene and is carried out by the Waste and Waste Management Section. Waste management for the Traditional Market area is also carried out by the local Market Service and for the kelurahan or village level to RW the hygiene management is the responsibility of the local community. This research aims to examine and analyze the effect of culture orientation and social support on work behavior, work value and performance of family waste management In Tegal Regency. The population in this study were 402 people managing household waste in Tegal Regency. The sample selection method uses purposive sampling method. The number of samples in this study were 200 people managing household waste in Tegal Regency. This study uses data analysis Descriptive Statistics, Test Assumptions, Structural Equation Modeling Analysis. Technique of data analysis using SEM with SPSS version 23 and AMOS 20. Based on the results of the research analysis it can be proven that Cultural orientation has no significant effect on work values, Social support has a significant effect on work values, Cultural orientation has a significant effect on work behavior, Social support has a significant effect on work behavior, Cultural orientation has no significant effect on performance, Social support has a significant effect on performance, Work values has no significant effect on performance, and Work behavior has no significant effect on performance.